Sero-prevalence of hepatitis B virus and compliance with hepatitis B vaccination schedules among outpatient clinic attendees in Nairobi. - Benard Langat; Edward K Muge; Doris Night; Fredrick Okoth; Kevin O Ochwedo; Elijah M Songok (PLoS ONE, 2023)
Background Hepatitis B is becoming a growing public health problem in Kenya. To combat the threat, HBV vaccination should be recommended, particularly for individuals who are not covered by the national immunization program. Vaccination provides sero-protection rates approaching 95% among healthy adults after completing the three-dose vaccination course, but decreases to 87% among those who receive only two doses, emphasizing the importance of completing the three-dose vaccination course. However, data on adult adherence to HBV multi-dose vaccines in Sub-Saharan Africa are limited, despite the fact that this information is critical for prevention. As a result, more research on HBV vaccine dose completion is required. The purpose of this study is to estimate the prevalence of hepatitis B virus infection among out-patient clinic attendees in Nairobi, Kenya, as well as to identify beneficiaries of free vaccination and barriers to completing the recommended vaccine doses. Methods Between July 30th and September 30th, 2015, 2644 outpatient clinic attendees aged ≥ 4 were recruited from three hospitals in Nairobi County, Kenya: Mama Lucy, Riruta, and Loco. Self-administered questionnaires were used to collect socio-demographic information, and blood samples were tested for hepatitis B surface antigen (HBsAg) using the KEMRI HEPCELL Rapid® (Hepatitis B Detection kit) test kit. Individuals who tested negative for HBsAg were given a free course of three doses of HBV vaccine. The vaccination register provided information on the number of doses administered. Results The average age of the study population was 31.4 years (range: 4-66), with females accounting for 59.2%. 1.82% (48/2644) of the participants tested positive for HBsAg. Among the 2596 individuals eligible for vaccination, 66% (1720/2596) received at least one dose, and 51.8% (1345/2596) received all three doses. Vaccination acceptance increased with age, with older patients more likely to return for subsequent dose (OR>1 for second and third dose). Unavailability and failure to contact client were cited as significant (p<0.0001) barrier to vaccination completion by 53.7% (666/1226, 95% CI 0.5-0.6) and 37% (454/1226, 95% CI 0.3-0.4) of respondents respectively. Conclusion The prevalence of HBV infection among outpatient clinic attendees highlights the importance of expanding HBV immunization programs in Kenya. However, given the low vaccination completion rate, there is a need for public awareness of the vaccine's importance in preventing HBV and HBV-related complications.